Selecting technologies to engage in sustainability transitions—A multi-stakeholder perspective - Carolin Block; Michael Rennings; Stefanie Bröring (Business Strategy and the Environment, 2022)
Given the need for systemic changes to reach a sustainability transition from a fossil-based toward a bio-based economy, it is crucial to align different actors' expectations along the value chain when developing and commercializing sustainability-oriented technologies (SOTs). To analyze what different actors along the value chain look for when selecting SOTs, this study draws upon a group concept mapping approach based on a group discussion and a subsequent sorting and rating process of selection criteria. Applied to the case of the bio-based economy, this study seeks to aggregate the perceptions of four different stakeholder groups along the value chain, that is, (1) agricultural and feedstock, (2) (bio)chemical, (3) consumer industries, and (4) consultancies and networks. We derive 11 different categories subsuming 59 criteria that have been perceived as relevant when selecting SOTs. Results show that selection criteria related to the future competitiveness, the public acceptance, and the sustainability aspects of the technology are perceived as highly relevant for most actors when selecting SOTs. Further, we summarize the 11 categories into four dimensions involving (1) market environment and viability, (2) corporate strategy and technology integration, (3) capabilities and knowledge exchange, and (4) institutional and regulatory frames related criteria. We contribute to sustainability transition literature by providing, first, a conceptual framework for relevant selection criteria of SOTs from a value chain spanning perspective; and second, areas of coherence versus noncoherence in technology evaluation across different value chain actors allowing targeted support initiatives to facilitate the technology transfer in the context of sustainability transitions.
Keywords: 330; bio-based economy; business stakeholder; group concept mapping; sustainability transition; technology selection